Current insights into functions of phospholipase A2 receptor in normal and cancer cells: More questions than answers. (June 2019) - Sukocheva, Olga; Menschikowski, Mario; Hagelgans, Albert; Yarla, Nagendra Sastry; Siegert, Gabriele; Reddanna, Pallu; Bishayee, Anupam
Abstract: Lipid signaling network was proposed as a potential target for cancer prevention and treatment. Several recent studies revealed that phospholipid metabolising enzyme, phospholipase A2 (PLA2 ), is a critical regulator of cancer accelerating pathologies and apoptosis in several types of cancers. In addition to functioning as an enzyme, PLA2 can activate a phospholipase A2 receptor (PLA2R1) in plasma membrane. While the list of PLA2 targets extends to glucose homeostasis, intracellular energy balance, adipocyte development, and hepatic lipogenesis, the PLA2R1 downstream effectors are few and scarcely investigated. Among the most addressed PLA2R1 effects are regulation of pro-inflammatory signaling, autoimmunity, apoptosis, and senescence. Localized in glomeruli podocytes, the receptor can be identified by circulating anti-PLA2R1 autoantibodies leading to development of membranous nephropathy, a strong autoimmune inflammatory cascade. PLA2R1 was shown to induce activation of Janus-kinase 2 (JAK2) and estrogen-related receptor α (ERRα)-controlled mitochondrial proteins, as well as increasing the accumulation of reactive oxygen species, thus leading to apoptosis and senescence. These findings indicate the potential role of PLA2R1 as tumor suppressor. Epigenetic investigations addressed the role of DNA methylation, histone modifications, and specific microRNAs in the regulation of PLA2R1 expression. However, involvement of PLA2R1 in suppression of malignant growth and metastasis remains controversial. In this review, we summarize the recent findings that highlight the role of PLA2R1 in the regulation of carcinogenesis-related intracellular signaling.